Temporal Temperature Variation in Urban Gardens Is Mediated by Local and Landscape Land Cover and Is Linked to Environmental Justice - Nolte, Alejandro Castillo; Buchholz, Sascha; Pernat, Nadja; Egerer, Monika (Frontiers in Sustainable Food Systems, 2022)
The urban heat island (UHI) effect remains a major threat to society as cities densify and sprawl. Urban greening through local to landscape management is a proposed strategy to combat UHI and improve environmental justice in city neighborhoods. For example, urban community gardens are multifunctional green spaces that play an important role for biodiversity and for civic engagement. But the role of urban gardens in urban cooling and relieving UHI remain unclear, specifically how temperatures fluctuate within gardens in relation to garden management factors and city landscape context, and how this relates to urban heat in city neighborhoods. We investigated diurnal and nocturnal temperature ranges, and daily maximum and minimum temperatures in 18 urban gardens over the peak of the summer agricultural growing season. We then analyzed how temperatures were correlated to local land cover factors within the garden, to surrounding landscape imperviousness at various spatial scales, and to environmental justice indicators (stressors) of garden neighborhoods. We found that nocturnal temperature range is negatively correlated to landscape imperviousness, and that the relationship decreases in strength with increasing spatial scale. This result supports the importance of evapotranspiration processes of surrounding green areas for nocturnal cooling. Some local land cover factors were important for temperatures, indicating heating or cooling management mechanisms from within urban gardens. Finally, the mean number of environmental stressors in neighborhoods negatively related to temperature variation. The results of this work can inform resource use and crop selection in urban agriculture, as well as how temperature-related ecosystem services of gardens relate to environmental justice of city neighborhoods.